2x + 3y = -5
3x + 4y = -8
in order of operations by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

2 Answers

2x + 3y = -5 --- (1)
3x + 4y = -8 --- (2)

From (2), we have:

4y = -3x - 8
y = (-3/4)x - 2 --- (3)

Substituting (3) into (1), we have:

2x + 3((-3/4)x - 2) = -5
2x - (9/4)x - 6 = -5
(-1/4)x = 6 - 5
(-1/4)x = 1
x = 1 * (-1/4)
x = -4

Substituting x = -4 into (3), we have:

y = (-3/4)(-4) - 2
y = 3 - 2
y = 1

Hence, x = -4 and y = 1.
by
Y=11/18 X=41/18 Hence proved..
by

Related questions

1 answer
asked Apr 16, 2019 in Algebra 2 Answers by sebestian junior | 600 views
2 answers
asked Jul 21, 2014 in Algebra 2 Answers by anonymous | 385 views
1 answer
asked Dec 6, 2013 in Algebra 1 Answers by vikas yadav | 4.5k views
1 answer
asked Oct 2, 2013 in Algebra 1 Answers by anonymous | 366 views
1 answer
asked Jul 14, 2013 in Algebra 2 Answers by rinee Level 1 User (120 points) | 323 views
1 answer
asked Dec 31, 2012 in Algebra 1 Answers by anonymous | 462 views
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
86,303 questions
92,362 answers
2,251 comments
23,927 users